Potential Role of Phosphoglycerol Dihydroceramide Produced by Periodontal Pathogen Porphyromonas gingivalis in the Pathogenesis of Alzheimer’s Disease - Yamada, Chiaki; Akkaoui, Juliet; Ho, Anny; Duarte, Carolina; Deth, Richard; Kawai, Toshihisa; Nichols, Frank; Lakshmana, Madepalli K.; Movila, Alexandru (Frontiers in Immunology, 2020)
Background: Among different types of sphingolipids produced by human cells, the possible engagement of ceramide species in the pathogenesis of Alzheimer’s disease (AD) has attracted recent attention. While ceramides are primarily generated by de novo synthesis in mammalian cells, only a limited number of bacterial species, produce ceramides, including phosphoglycerol dihydroceramide (PGDHC) that is produced by the key periodontal pathogen Porphyromonas gingivalis. Emerging evidence indicates that virulence factors produced by P. gingivalis, such as lipopolysaccharide and gingipain, may be engaged in the initiation and/or progression of AD. However, the potential role of PGDHC in the pathogenesis of AD remains unknown. Therefore, the aim of this study was to evaluate the influence of PGDHC on hallmark findings in AD. Material and Methods: CHO-7WD10 and SH-SY-5Y cells were exposed to PGDHC and lipopolysaccharide (LPS) isolated from P. gingivalis. Soluble A𝛽42 peptide, amyloid precursor protein (APP), phosphorylated tau and senescence-associated secretory phenotype (SASP) factors were quantified using ELISA and Western blot assays. Results: Our results indicate that P. gingivalis (Pg)-derived PGDHC, but not Pg-LPS, upregulated secretion of soluble Aβ42 peptide and expression of APP in CHO-7WD10 cells. Furthermore, hyperphosphorylation of tau protein was observed in SH-SY-5Y cells in response to PGDHC lipid. In contrast, Pg-LPS had little, or no significant effect on the tau phosphorylation induced in SH-SY-5Y cells. However, both PGDHC and Pg-LPS contributed to the senescence of SH-SY5Y cells as indicated by the production of senescence-associated secretory phenotype (SASP) markers, including beta-galactosidase, cathepsin B (CtsB), and pro-inflammatory cytokines TNF-α, and IL-6. Additionally, PGDHC diminished expression of the senescence-protection marker sirtuin-1 in SH-SY-5Y cells. Conclusions: Altogether, our results indicate that P. gingivalis-derived PGDHC ceramide promotes amyloidogenesis and hyperphosphorylation, as well as the production of SASP factors. Thus, PGDHC may represent a novel class of bacterial-derived virulence factors for AD associated with periodontitis.